Alternating Current Electrolysis Enabled Formal C−O/O−H Cross‐Metathesis of 4‐Alkoxy Anilines with Alcohols. Issue 18 (7th March 2022) - Wang, Daoxin; Jiang, Tengfei; Wan, Hao; Chen, Ziyue; Qi, Junchao; Yang, Anqi; Huang, Zhiliang; Yuan, Yong; Lei, Aiwen
Abstract: While multiple bond metathesis reactions, for example olefin metathesis, have seen considerable recent progress, direct metathesis of traditionally inert C−O single bonds is extremely rare and particularly challenging. Undoubtedly, metathesis reaction of C−O bonds is one of the most ideal routes for the value‐added upgrading of molecules involving C−O bonds. Reported here is a new protocol to achieve the formal C−O/O−H cross‐metathesis via alternating current electrolysis. Featuring mild reaction conditions, the protocol allows readily available 4‐alkoxy anilines and alcohols to be converted into a wide range of valuable products in highly regioselective and chemoselective manner. Moreover, the present strategy can be used in the late‐stage modification of pharmaceuticals as well as biologically active compounds, which demonstrated the potential application. Abstract : A novel alternating current promoted formal C−O/O−H cross‐metathesis reaction of 4‐alkoxy anilines with alcohols has been developed for the first time.